Quality Evaluation and Determination of Possible Adulterants in Various Marketed Butter Oil and Ghee in Bangladesh - Kumar, Bijon; Saqueeb, Nazmus; Sikdar, K M Yasif Kayes; Ahmed, Firoj; Faroque, ABM (Bangladesh Journal of Nutrition, 2019)
Butter oil is a dairy product with high butter fat content that turns into solid when chilled and liquid when warmed. Ghee is a class of clarified butter originated in primitive India. Both butter oil and ghee are widely used for cooking various foods as well as food supplement in Bangladesh. However, low-quality butter oil and ghee may cause serious health hazard to the population who consumes regularly. In the present study, the physicochemical parameters of marketed butter oil and ghee samples were analyzed and results were compared with Bangladesh Standards and Testing Institution (BSTI)standard. Three (3) samples of butter oil (B-1 to B-3) and 24 samples (G-1 to G-24) of ghee were collected from different local market of Bangladesh. The quality determinant parameters like moisture content, acid value and free acid value, iodine value, saponification value, peroxide value and presence of sesame oil were analyzed. All the samples of butter oil and ghee were failed to meet the standard value of moisture content (butter oil, < 0.5% and ghee, < 0.1%), saponification value (> 218 mg/gm) and sesame oil test (negative) compared to the BSTI standard. However, among all 27 samples only one sample of ghee, G-7 (35.01) met the limit of iodine value (26-35) compared to the BSTI standard. Rest of the parameters like acid value (< 1.9 mg/gm), free acid value and peroxide value (< 0.8 mEq of O2/kg) were within the limit of BSTI standard for all the samples. However, every parameter needs to be within the BSTI standard limit to ensure the quality of butter oil and ghee. So, more concern is needed by the government authority to ensure the proper quality of marketed butter oil and ghee in Bangladesh. Bangladesh J. Nutr. Vol. 32, December 2019, P: 15-23